Transcriptome Analysis Reveals a Gene Expression Pattern That Contributes to Sugarcane Bud Propagation Induced by Indole-3-Butyric Acid - Xu, Lin; Deng, Zhi-Nian; Wu, Kai-Chao; Malviya, Mukesh Kumar; Solanki, Manoj Kumar; Verma, Krishan K.; Pang, Tian; Li, Yi-Jie; Liu, Xiao-Yan; Kashyap, Brijendra Kumar; Dessoky, Eldessoky S.; Wang, Wei-Zan; et al. (Frontiers in Plant Science, 2022)
Abstract Sugarcane is a cash crop that plays an integral part in the sugar industry. The Sustainable Sugarcane Initiative (SSI) has been adopted globally, ensuring enough and aiming for more yield, helping increase disease-free sugarcane cultivation. Single bud seeds could be the best approach for sugarcane cultivation. Indole-3-butyric acid (IBA) is a rooting agent utilized significantly in seedling propagation. Greenhouse experiment results discovered the significant growth promotion in sugarcane seedlings and accumulation of plant hormones at 100 ppm IBA. Next, we performed transcriptomic analysis of sugarcane buds using RNA sequencing and compared their gene expression during root development due to affect of IBA (100 ppm). A total of 113,475 unigenes were annotated with an average length of 836 bp (N50=1536). The comparative RNAseq study between the control (CK) and IBA treated (T) buds showed significant differentially expressed unigenes (494 up-regulated and 2086 down-regulated). The IBA influenced major biological processes including metabolic process, the cellular process, and single-organism process. For cellular component category, cell, cell part, organelle, membrane and organelle part are mainly affected. In addition, catalytic activity and binding were primarily affected in the molecular function categories. Furthermore, the expression of genes related to plant hormones and signaling pathways was analyzed by qRT-PCR, which was consistent with the RNA-seq expression profile. This study provides new insights into the IBA response to the bud sprouting in sugarcane based on RNA sequencing, and generated information could help further research on breeding improvement of sugarcane.